House bulb light-induced photochemical acetalization of carbonyl compounds catalyzed by Eosin Y. Issue 9 (3rd May 2018) - Zhou, Quan; Jia, Tao; Li, Xiao-Xuan; Zhou, Lin; Li, Chang-Jiang; Feng, Yi-Si
ABSTRACT: We have systematically studied the reactions of acetalization and found that high reaction efficiency can be achieved using cheap and readily available organic Eosin Y as catalyst. The reaction proceeds smoothly under house bulbs and shows excellent functional group tolerance. The substrates of the reaction system are compatible with aromatic aldehydes, aliphatic aldehydes, aromatic ketones, and cyclic ketones with high yields. GRAPHICAL ABSTRACT: